Menanamkan Karakter Cinta Lingkungan Pada Anak Usia Dini Dengan Media Ecobrick Botol Di SPS Sirojul Muttaqin - Jubaedah, Endah; Fuadah, Apipah samrotul (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
This research is based on observational data showing that the character of environmental awareness in early childhood at SPS Sirojul Muttaqin has not yet developed optimally. Several issues were identified, including a lack of environmental awareness among children and the limited variety of media used by teachers, which resulted in insufficient stimulation of children's love for the environment. The purpose of this study is to describe how to instill environmental awareness in early childhood using ecobrick bottle media at SPS Sirojul Muttaqin. Additionally, the researcher aims to determine the effectiveness of this media in fostering children's environmental character. The study involved 25 respondents, consisting of 14 boys and 11 girls. This research employs a quantitative approach using a pre-experimental design, specifically the one-group pretest-posttest design. The results indicate a significant increase in children's environmental awareness after the implementation of ecobrick bottle media. This is supported by data analysis using the SPSS program, which showed a significance value of 0.000—less than 0.005—indicating that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Keywords: early childhood, environmental awareness character, ecobrick